Justice is What Spacetime Literally Creates: Justice as a Space - Hamidi, Nabil (My University, 2025)
Spacetime originates or creates justice for three clear empirical principles: chronological priority, ontological independence, and necessary condition analysis. First, science agrees that justice originated in spacetime: justice systems emerged within a spatial environment, as all forms of justice were made possible only because spatial conditions already existed. Second, justice cannot exist without spacetime, while spacetime has clearly existed without justice. The second principle is universally recognized by scientists: spacetime is a physical precondition, whereas justice is a later, emergent phenomenon. Third, science agrees that no form of human justice—nor any form of justice whatsoever—preceded spacetime. Spacetime existed 14 billion years ago, long before the appearance of any justice system. Therefore, because spacetime predates all justice, because justice depends on distance for its existence, and because spacetime did not depend on justice, the conclusion follows directly: spacetime originates justice; thus, justice is a spacetime.
The Spatial Transformation of Justice